Historical processes of chemical blackening of steel and their corrosion resistance - Rapouch, Karel; Trčka, Josef; Selucká, Alena; Foret, Lukáš (Korose a ochrana materiálu, 2024)
This study focuses on the evaluation of historical acid blackening of steel in terms of their applicability to historical objects, such as tin-soldered multi-barrelled firearms, where the alkaline bath blackening method cannot be used. The acid blackening method was also compared with the alkaline hot bath blackening method used nowadays, both on the conversion layer itself and in combination with a preservative agent. The procedures were tested on low carbon steel samples and fragments of damaged historic steel barrels. The quality of the surface treatment was evaluated both in terms of visual appearance and corrosion resistance. The corrosion properties were evaluated both by a condensation chamber test and by electrochemical methods such as polarization resistance measurements or electrochemical impedance spectroscopy.